Extending the interval between second vaccination and slaughter: II. Changes in the reproductive capacity of immunocastrated ram lambs. (17th January 2019) - Needham, T.; Lambrechts, H.; Hoffman, L. C.
Abstract : Immunocastration improves the welfare of castrated commercial slaughter lambs; however, the time-point at which this technique influences semen quality and sperm production has not yet been established for various vaccination schedules. Furthermore, the effect of extended intervals between second vaccination and slaughter needs to be investigated regarding continued testosterone suppression in immunocastrated lambs. The effect of extending the interval between second immunocastration vaccination and slaughter from four to six weeks on the reproductive capacity of Dohne Merino lambs was examined. A total of 40 Dohne Merino lambs were stratified according to initial weight (45.4±3.68 kg) and randomly assigned to four treatments that included intact control rams (R), Burdizzo-castrated lambs (B) and lambs immunocastrated with either four (ICS4) or six (ICS6) weeks between second vaccination and slaughter. Blood and semen samples were collected throughout the study period to determine serum testosterone concentrations, evaluate semen quality and assess sperm viability. Semen samples from R showed improvement over the trial. Throughout the collection period, B lambs had low serum testosterone concentrations, poor sperm motility and sperm viability, as expected. However, a slight increase in the percentage of live sperm in semen samples from B lambs towards the end of the collection period indicated poor success rates of the technique in some lambs. Burdizzo-castration also caused testes tissue necrosis and abscessing, indicating physiological stress. Semen appearance scores varied for both immunocastrated treatments, but the mass motility scores decreased over time. The ICS6 lambs showed a consistent and continuous decline in serum testosterone concentrations and sperm viability, with an increased percentage of dead abnormal sperm in the semen samples at the end of the study. The ICS4 treatment was successful in interrupting serum testosterone production and reducing semen quality; however, not as consistently as the ICS6 treatment. Primary immunocastration vaccination influenced serum testosterone concentrations but consistently low levels were only realised for both treatments after secondary vaccination. Although all castration treatments influenced testes size and colour, the six-week vaccination-to-slaughter interval caused a greater decrease in testes cut surface L * (lightness) colour values and in seminiferous tubule circumference. Extending the interval between second immunocastration vaccination and slaughter resulted in a more consistent and reliable influence on reproductive capacity of immunocastrated lambs. Thus, immunocastration is a suitable alternative to Burdizzo-castration regarding the interruption of testosterone production and testis functioning.